The Fisheries Co-Management Guidebook: Emerging research for the effective management of small-scale fisheries - Smallhorn-West, Patrick; Abesamis, Rene; Notere Boso, Delvene; Cinner, Joshua; Cohen, Philippa; Gelcich, Stefan; Harrison, Hugo; Jones, Geoffrey; Jupiter, Stacy; Khan, A K M Firoz; Lau, Jacqueline; Lawless, Sarah; et al. (WorldFish, 2023)
Small-scale fisheries account for 40% of global fish catch and employ more than 90% of the world’s fishers, defining the livelihoods, nutrition, and culture of a substantial and diverse segment of humankind. In recent decades collaborative forms of fisheries management, including co-management, have gained popularity as the most appropriate, fair, and effective form of governance for small-scale fisheries. Fisheries co-management is envisioned as a process by which to reverse the interconnected crises of hunger, poverty, and biodiversity loss, transforming small-scale fisheries into engines of prosperity, inclusion, and sustainability. Yet co-management can succeed or fail, and implementation does not mean positive impacts for food security, nutrition, livelihoods, or biodiversity. Nor does it imply programs will respect human rights, gender equality, or principles of justice and equity. Fewer management programs implemented well might achieve far more than many implemented poorly, and poorly implemented co-management can be worse than no management. This guide was designed to assist practitioners in understanding the latest research on what constitutes successful fisheries co-management, and how to reach this objective. The aim is to synthesize emerging research that, if adopted, would substantially improve impacts across both ecological and social dimensions. The guide is presented as an infographic series with each infographic summarizing a substantial body of research from a particular field. This work was undertaken through a growing partnership between the Wildlife Conservation Society and WorldFish, aiming to increase collaboration between conservation and development sectors. This partnership represents a milestone towards integrated approaches for the benefit of both ecosystems and local communities.